HUBUNGAN KECEPATAN DAN KELINCAHAN DENGAN KETERAMPILAN DRIBBLING DALAM PERMAINAN SEPAKBOLA PADA TIM SMP NEGERI 40 PEKANBARU - Zekri, Robby Kurniawan; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research was to find out the correlation between agility in dribbling, and to find out the correlation between speed and agility in dribbling in football team of SMPN 40 Pekanbaru. This research was correlational research. The population on this research was 20 students in football team of SMPN 40 Pekanbaru. To get the data, the researcher asked the students did sprint 40 yards test to know their speed, dodging run test to know their agility and dribbling test. The obtained data was analyzed with a simple product of moment correlation. Based on the analysis, the r(count) = 0,605 > from r (table) 0,444. Therefore, Ha was accepted and Ho was rejected. It can be concluded that there was a relationship between speed and agility in dribbling which can be determined from r (count) > r table and significantly determined by the correlation between one to another variable.Keywords: Speed, Agility, Dribble, Football